Hyperandrogenism-related metabolic changes in drug-naïve transmen compared to cisgender women: a case-controlled study - EREL, PINAR; ELBASAN, ONUR; YORGUNER, NEŞE; İMRE, EREN; ÜSTAY, ÖZLEM (My University, 2023)
Introduction: The aetiology of gender dysphoria is still unclear. Although prior studies have shown that trans men have higher androgen levels than cisgender women, they all concluded unselected populations. Our reason for performing this study is to evaluate trans men’s hormone profile and metabolic status to compare with cisgender women in a more selected population. This is the first case-controlled study to compare anthropometric, metabolic, and endocrinological parameters of drug-naïve trans men with those of cisgender women. Material and methods: We designed this study as a single-centre observational cohort study. We included 70 drug-naïve trans men, and the control group comprised 34 healthy cisgender women. We measured and compared hormone profiles and metabolic parameters in the 2 groups. Results: Of the 70 trans men individuals, 16 (22.85%) met the Rotterdam criteria and were diagnosed with polycystic ovary syndrome (PCOS); 4 individuals in the control group met the criteria (11.7%). Although we matched body mass index in the groups, total testosterone, free androgen index, androstenedione, 17 hydroxyprogesterone, muscle strength, triglyceride, and homeostatic model assessment of insulin resistance levels were significantly higher in the trans men than in the cisgender women (p < 0.05). Even after were excluded PCOS patients, hyperandrogenaemia was apparent in the trans men. Conclusion: Our study showed that trans men have clearly higher androgen levels, which may have been the reason for metabolic changes compared to cisgender women. However, the main reason for hyperandrogenism in drug-naïve trans men is still not known, and more comprehensive studies are needed.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ENDOKRİNOLOJİ VE METABOLİZMA; Clinical Medicine (MED); CLINICAL MEDICINE; ENDOCRINOLOGY & METABOLISM; Endokrinoloji, Diyabet ve Metabolizma; Endokrinoloji; Yaşam Bilimleri; Endocrinology, Diabetes and Metabolism; Endocrinology; Life Sciences; androgen; cisgender women; metabolic syndrome; trans men